Synthesis and properties of hyperbranched polyimides derived from novel triamine with prolonged chain segments. Issue 11 (19th March 2013) - Shen, Jie; Zhang, Ying; Chen, Wenqiu; Wang, Wenhao; Xu, Zushun; Yeung, Kelvin W. K.; Yi, Changfeng
ABSTRACT: Novel pyridine‐containing hyperbranched polyimides (HBPIs) were synthesized by using a new triamine 2, 4, 6‐tris[3‐(4‐aminophenoxy)phenyl]pyridine with prolonged chain segments, ether linkage and meta ‐linked units as a BB′2 ‐like monomer, various commercial aromatic dianhydrides as A2 monomers. Most of the obtained HBPIs were readily soluble in common organic solvents such as N, N ‐dimethylformamide, N, N ‐dimethylacetamide, N ‐methyl‐2‐pyrrolidone, m ‐Cresol, and so forth. Meanwhile, they also had good thermal stability with the glass transition temperatures ( T g s) all above 210 °C, the temperature at 10% weight loss of 537.1–574.4 °C in nitrogen atmosphere. Strong and flexible HBPI films were obtained, which had good mechanical properties with tensile strengths of 83.3–95.8 MPa, tensile modulus of 1.82–2.43 GPa and elongations at break of 4.84–6.98%. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 2425–2437 Abstract : A novel pyridine‐containing triamine 2, 4, 6‐tris[3‐(4‐aminophenoxy)phenyl]pyridine with prolonged chain segments, ether linkage, and meta ‐linked units is synthesized and employed to prepare a series of amine‐ and anhydride‐terminated hyperbranched polyimides (HBPIs). The HBPIs inherit excellent thermal properties and exhibit high solubility and good mechanical properties. These superior properties will be favorable in further research.